Decentralization vs Centralization: Scenarios of Regional Development of Ukraine in the Context of Internal Stability Establishment - Uzun, Yuliia; Koch, Svetlana (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The work aims to analyze scenarios for the development of regional policy in Ukraine in conditions of decentralization and centralization trends confrontation in the country. The main problem is the establishment of structural completeness of the decentralization reform in Ukraine, which should involve the implementation of administrative-territorial, budgetary and political decentralization. An important task is also to determine the effectiveness of devolution, delegation, deconcentration, deregulation, and divestment, which are manifestations of the decentralization process and collectively determine the quality of reform. Based on the methodology of system analysis and the concept of “balance of relations,” as well as using a historical and comparative method in investigating the improvement of approaches to leading public policy, and a structural-functional method for analysis of territorial-political system as a decentralized and multi-level, the paper proposes an analysis of the balance of inter-level relations in the country, the effectiveness of reforms, decentralization and trends for further development. The work indicates that since 2014, administrative and territorial optimization and enlargement of communities have become the main result of the decentralization reform. The discussion of political decentralization remains extremely disturbing and is blocked as “separatism,” as well as attempts to resolve the conflict in the Donbas by political means through the adoption of the Steinmeier Formula are demurred as “capitulation.” The economic crisis, which coincided with the pandemic, can aggravate the negative perception of reform, the development of which remains possible within the framework of three development scenarios: “Euro-optimistic,” “inertial” and “blocking.”

Celem badania jest analiza scenariuszy rozwoju polityki regionalnej na Ukrainie w obliczu sprzeciwu wobec trendów decentralizacji i centralizacji. Głównym problemem jest ustalenie strukturalnej kompletności reformy decentralizacji na Ukrainie, która powinna obejmować wdrożenie decentralizacji administracyjno-terytorialnej, budżetowej i politycznej. Zadanie polega również na określeniu skuteczności decentralizacji, delegacji, dekoncentracji, deregulacji, dywersyfikacji, które są przejawami procesu decentralizacji i zbiorowego określania jakości reformy. Na podstawie metodologii analizy systemowej i pojęcia „równowagi relacji”, w artykule wykorzystano metodę historyczno-porównawczą w badaniu doskonalenia podejść do prowadzenia polityki publicznej oraz strukturalno-funkcjonalną metodę analizy systemu terytorialno-politycznego jako zdecentralizowanego i wielopoziomowego, w celu przedstawienia analizy równowagi wewnętrznych stosunków między poszczególnymi poziomami, oraz omówienia skuteczności reform, decentralizacji oraz trendów dalszego rozwoju. Prace wskazują, że od 2014 r. optymalizacja administracyjna i terytorialna oraz konsolidacja społeczności stały się głównym wynikiem reformy decentralizacyjnej. Dyskusja na temat decentralizacji politycznej jest niezwykle bolesna, podobnie jak próby rozwiązania konfliktu w Donbasie środkami politycznymi poprzez przyjęcie tzw. formuły Steinmeiera. Kryzys gospodarczy, który zbiegł się z pandemią, może spotęgować negatywne postrzeganie reformy, której rozwój jest możliwy w ramach trzech scenariuszy rozwoju: “euro-optymistycznego”, “bezwładnościowego” i “blokującego”.
Decentralizacja vs centralizacja. Scenariusze rozwoju regionalnego Ukrainy w kontekście zapewnienia stabilności wewnętrznej
Keywords: decentralization; centralism; regionalism; self-government; Ukraine; decentralizacja; centralizm; regionalizm; samorząd; Ukraina